EFFECT OF MALE TO FEMALE RATIO AND VITAMIN-E SELENIUM SUPLEMENTATION ON EGG PRODUCTION AND EGG WEIGHT OF JAPANESE QUAIL (Pakistan Journal of Science, 2025)
The aim of this study was to examine the effect of mating ratio (male: female) and vitamin E -Selenium supplementation on egg production and egg weight of quail breeders. Total 720 Japanese quails of ten weeks of age with an average of 50% egg production were divided into four groups A, B, C and D having male: female mating ratio of 1:1, 1:2, 1:3 and 1:4 respectively. All the four groups were further sub-divided into vitamin E -Selenium supplemented (at the rate of 1ml/6 liters of drinking water) and control sub-groups. Each sub-group was further replicated three times with 30quails/replicate. Egg production was significantly (P
Keywords: Male to female ratio; vitamin E -Selenium; egg production; egg weight; quails